Irregular total labeling on complete bipartite graph and union complete bipartite graphs - Daoud, Jamal Ibrahim; ,, Wamiliana; Usman, Mustofa; ,, Asmiati (University of Allahabad, 2010)
Given a graph with vertex set V and edge set E, we define a labeling as a function, where weight of edge xy is written as Total labeling is the sum of xy-label and labels of the vertices that incident to x, thus l labeling is called as edge irregular total k-labeling of the graph G if for every two different edges e and f of G, The smallest k in which graph G can be labeled as edge irregular total k-labeling is called as edge total irregularity strength and is noted as In this research, we are interested in finding of the union of complete bipartite graphs...